Taxonomic aggregation and the detection of patterns in a tropical marine benthos data set - Guzmán, Angela (1996)
Soft-bottom benthic abundance data were aggregated from genera to phylum and the effect of such aggregation in the detection of a depth related pattern explored. It was found that at least for this data set, the aggregation has no effect, the pattern being clear across the taxonomic aggregations. If this is a general feature of tropicaI soft-bottom rapid assessments, for instance in the case of quick surveys or pollution events, would be possible.